Percepção da paisagem e diretrizes de planejamento urbano como proposta de melhoria aos atrativos turísticos de Pinto Bandeira/RS - Toni, Daiane de (My University, 2019)
This paper aims to present the landscape potential of the Municipality of Pinto Bandeira. The proposal is related to urban planning guidelines to help reinforce the existing landscapes in the area traveled by tourists and residents. Thus, with the aim of attracting tourists who visit the region, the paper seeks to value the natural, cultural and cultivated beauties through landscape design oriented by the methodology developed from Kohlsdorf (1996), Alexander (2013) and Rigatti and Trusiani (2017). In the developed method, the visual effects, identification of the historical, cultural and landscape elements, and design guidelines in the construction of the proposal are addressed as a form of analysis to guide the paper through the approaches of each author. In addition, this research and the resulting project intend to stimulate the use of open spaces by the population and enhance the cultural identity of the municipality. [resumo fornecido pelo autor]
Este trabalho tem o intuito de demonstrar as potencialidades paisagísticas do Município de Pinto Bandeira. A proposta está relacionada com diretrizes de planejamento urbano para auxiliar a fortalecer as paisagens existentes no espaço compreendido pelo percurso percorrido por turistas e moradores. Assim, com o objetivo de atrair os turistas que visitam a região, o trabalho busca valorizar as belezas naturais, culturais e cultivadas através do desenho da paisagem orientado pela metodologia desenvolvida por Kohlsdorf (1996). Neste método desenvolvido pela autora, são abordados os efeitos visuais e o comportamento topoceptivo como forma de análise para orientar o trabalho. Além disso, a pesquisa pretende estimular o uso dos espaços abertos pela população e fortificar a identidade cultural do município. [resumo fornecido pelo autor]
Keywords: Planejamento urbano - Pinto Bandeira (Bento Gonçalves, RS); Arquitetura; Arquitetura paisagística; Turismo